Understanding the creative capability of the humane being in the reportagessay - Osorio Vargas, Raúl Hernando (Folios, revista de la Facultad de Comunicaciones y Filología, 2018)
In this essay, we discuss the potential of the reportagessay as a praxis fit to the efforts for understanding a reality of complex build. Thus, we propose its principles from the perspective of Cremilda Medina's concept of Humane Being and the criticism on the objectivist view of reality as stated by Fritjof Capra. More than a journalistic genre, we propose reporting ethics substantially based on the dialogue between the reporter and subjects on the move who live in a world of changing and transculturation.